Phenomenological Study: Marriage Satisfaction on Wife Who Has Long-Distance Marriage - Zuhrina Ramadhani; Nur’aeni Nur’aeni (Proceedings Series on Social Sciences & Humanities, 2021)
This study was conducted to describe marital satisfaction in wives who run distant marriages. This research focuses on the marital satisfaction of the wife who undergoes a foreign marriage because her husband works outside Java. This research is qualitative research with a phenomenological approach, data collection using in-depth interview techniques on the main subject. The credibility of data using research extension and data triangulation. Participants have two wives with the criteria that a wife and husband work outside Java. The results of research conducted on 2 participants show that despite undergoing long-distance marriages, participants N and S can communicate well via telephone or chat and are open to each other in communication with their partners. Participants take advantage of their free time with quality time with their partners. Participant S is not satisfied with applying religious values, while Participant N is satisfied with their partner's religious values. Participant N and Participant S resolve conflicts by being creative and finding solutions together. Participants are open to each other in financial matters. Long-distance marriages support participants to fulfill their sexual needs by calling or video calling, showing affection for each other, and being open about sexual issues. Participants have a reasonably good relationship with family and friends due to frequent visits. Parenting is still carried out together by the participants both near and far. Participants can accept and respect each other's personality differences. Participants can receive the roles that must be carried out, such as being child protectors and independent when their husbands have to be away.